Food Habits of Indian Grey Hornbill Ocyceros birostris in Sathyamangalam forest Division, Eastern Ghats, India - Santhoshkumar, E.; Balasubramanian, P. (Journal of the Bombay Natural History Society (JBNHS), 2014)
The foraging ecology of Indian Grey Hornbill Ocyceros birostris was studied in Sathyamangalam Forest Division, Eastern Ghats, from 2006 to 2008. Its diet in the breeding season was assessed by 720 hours of direct observations of food deliveries to 10 different nest inmates and by nest midden analysis. Observations at nest holes revealed that males visited nests an average of 16 times per day, and the food items delivered to the nest inmates (female and chicks) included both plant (63.7%) and animal matter (36.3%). Fleshy fruits of 14 species were delivered, and the animal matter was mainly insects (99%). Seeds collected from the nest middens on analysis showed the presence of 26 fruit species of 16 plant families. Food habits of this hornbill during the non-breeding season were assessed by walking along transects and observing foraging activities. Of the 3,086 feeding observations obtained, 83% were on fruits and the rest were on leaves (8.8%), insects (7.7%), and flowers (0.5%). Of the 38 fruit species eaten, Ficus spp. constituted 25.3% of the non-breeding season fruit diet. In all, fruits of 41 species of 21 families were recorded in the diet. The study revealed that both fig and non-fig species are important for the survival of the Indian Grey Hornbill in the Eastern Ghats.